Epigenetic factors and inflammaging: FOXO3A as a potential biomarker of sarcopenia and upregulation of DNMT3A and SIRT3 in older adults - Bogucka, Diana; Wajda, Anna; Stypińska, Barbara; Radkowski, Marcin Jerzy; Targowski, Tomasz; Modzelewska, Ewa; Kmiołek, Tomasz; Ejma-Multański, Adam; Filipowicz, Gabriela; Kaliberda, Yana; Dudek, Ewa; Paradowska-Gorycka, Agnieszka (Frontiers in Immunology, 2025)
BackgroundEpigenetic factors influence inflammaging and geriatric disorders such as sarcopenia and frailty. It is necessary to develop a biomarker/panel of biomarkers for fast and easy diagnostics. Currently, hard-to-access equipment is required to diagnose sarcopenia. The development of a biomarker/panel of biomarkers will prevent many older adults from being excluded from the diagnostic process.MethodsIn this study, we analyzed selected gene expression profiles, namely, SIRT1, SIRT3, SIRT6, DNMT3A, FOXO1, FOXO3A, and ELAVL1, in whole blood. The study included 168 subjects divided into five groups: patients hospitalized at the Geriatrics Clinic and Polyclinic with sarcopenia, frailty syndrome, or without those disorders (geriatric control), and non-hospitalized healthy controls (HC) aged 25 to 30 years and over 50 years.ResultsWe revealed a lower mRNA level of FOXO3A (p<0.001) in sarcopenic patients compared to the geriatric controls. Furthermore, we detected upregulation of DNMT3A (p=0.003) and SIRT3 (p=0.015) in HC over 50 years old compared to HC aged 25 to 30 years. Interestingly, we observed 2 cluster formations during the gene expression correlation analysis (SIRT1, SIRT3, DNMT3A, and FOXO1, ELAVL1). We also noted correlations of clinical parameters with mRNA levels in the sarcopenic patients group, such as vitamin D level with SIRT1 (r=0.64, p=0.010), creatine kinase with SIRT3 (r=–0.58, p=0.032) and DNMT3A (r=–0.59, p=0.026), creatinine with DNMT3A (r=0.57, p=0.026), erythrocyte sedimentation rate (ESR) with FOXO3A (r=0.69, p=0.004), and lactate dehydrogenase (LDH) with FOXO3A (r=–0.86, p=0.007). In the frailty syndrome group, we noted a correlation of appendicular skeletal muscle mass (ASMM) with ELAVL1 (r=0.59, p=0.026) mRNA level. In the geriatric controls, we observed a correlation of serum iron with FOXO3A mRNA level (r=–0.79, p=0.036).ConclusionsOur study revealed FOXO3A as a potential biomarker of sarcopenia. Furthermore, we observed a high expression of epigenetic factors (DNMT3A and SIRT3) in older adults.